THE POPULATION IN 20TH CENTURY CENTRAL AMERICA: ANNUAL VITAL STATISTICS AND TOTAL POPULATION ESTIMATES - Pérez Brignoli, Héctor (2015)
This essay compiles and corrects annual vital statistics of Guatemala, El Salvador, Honduras, Nicaragua, and Costa Rica during the 20th century. Moreover, it presents and corrects census data of the total population. After 1950, it considers population data coming from CELADE to be reliable enough and useful for population projections for the period 1950-2050.